Population dynamics of Saissetia oleae. II. Life-tables and key-factor analysis - Kapatos, E. T.; Stratopoulou, E.T. (ENTOMOLOGIA HELLENICA, 1990)
A series of life-tables for the population of Saisselia oleae (Oliv.) (Homoptera: Coccidae) during five yearly generations (1981-86) were constructed in Corfu. Key-factor analysis carried out on the life-table data indicated that mortality of young stages during summer, caused mainly by the high temperatures, and mortality during spring, caused mainly by predation, determine total population change within each generation. These two mortality factors are the predominant factors of the population dynamics of S. oleae determining population fluctuations. The other mortality factors of the population system of S. oleae were less important. Summer parasites and egg predators, in particular, do not play any significant role on the population dynamics of S. oleae.